Kasus Kasus di Indonesia White Color Crime (WCC) - Husnil Mubarok Nst; Linda Safitri Lubis; Isna Damayanti Siagian; Sahlan Sahlan (LPPM Politeknik Pratama, 2024)
White-collar crime has been defined by Edwin Sutherland as